CD4/CD8 ratio normalization rates and low ratio as prognostic marker for non-AIDS defining events among long-term virologically suppressed people living with HIV - Han, Win Min (BioMed Central, 2018)
Background: Immune restoration is often incomplete after ART in HIV patients, both quantitatively and qualitatively.We studied the incidence and probability of CD4/CD8 normalization in an adult Thai HIV cohort and explored thepredictive value of the ratio for developing of non-AIDS defning events (NAEs).Methods: We analyzed data from HIV-infected Thai adults between 1996 and 2017 in the HIV-NAT 006 prospectivelong-term cohort in Bangkok, Thailand. Normalization was defned as CD4/CD8 ratio ≥1 on two consecutive visits,and normalization probability was calculated using the Kaplan–Meier method. NAEs were a composite endpointincluding cardiovascular or cerebrovascular diseases, chronic kidney diseases, non-AIDS defning malignancies anddeath. Multivariate Cox regression was used to evaluate demographic, disease and treatment characteristics associated with CD4/CD8 ratio normalization and NAEs.Results: A total of 800 ART-naïve patients with baseline CD4/CD8 ratio of <0.8 who started combination ART, andhad sustained virological suppression were enrolled. Participants were on ART for a median of 8.9 years and virologically suppressed for 6.1 years. The probabilities of CD4/CD8 normalization at 2, 5 and 10 years after virological suppression were 5.1%, 18.6% and 39.1%, respectively. Factors associated with normalization in multivariate analysis werefemale sex (hazard ratio [HR]: 2.47, 95% CI 1.71–3.56, p<0.001) and baseline CD4 counts ≥350 cells/mm3 (HR: 3.62,95% CI 2.36–5.55), p<0.001) vs. <200 cells/mm3 as reference. The second analysis explored the predictive value ofCD4/CD8 ratio for NAEs. Older age (HR: 1.09, 95% CI 1.05–1.13, p<0.01) and current CD4/CD8 ratio <0.3 (HR: 3.02, 95%CI 1.27–7.21, p=0.01) or between 0.3 and 0.45 (HR: 2.03, 95% CI 1.03–3.98, p=0.04) vs. >0.45 were independentlyassociated with higher risk of progression to NAEs in the multivariate analysis.Conclusions: Our fndings showed that complete immune recovery is uncommon in an Asian setting and earlierART initiation at higher CD4 counts may have increased the ratio sooner. The fndings demonstrate the use of CD4/CD8 ratio as a prognostic marker for clinical progression of NAEs.